Architecture Design in Energy Usage Efficiency Effort - Frysa Wiriantari; Arya Bagus Mahadwijati Wijaatmaja (Journal of Sustainable Development Science, 2020)
The current world condition where the availability of energy especially non-renewable energy is running low, we are required to be able to use available energy efficiently and as economically as possible. Amid the not yet socialized use of alternative energy, these demands are mandatory. One key to saving energy is the use of electrical energy to meet the needs of lighting and air conditioning. Some ways that can be done to save energy are through the management of utility systems, user behavior and consistency of knowledge related to energy-efficient buildings. Some of the principles used in energy-efficient development are minimizing fuel, adjusting to the surrounding climate conditions, using appropriate materials, while still providing comfort to the user. The method used in this research is a qualitative descriptive method focusing on efforts to minimize energy use in buildings.